Strange men, strange places - Bond, Ruskin (New Delhi Rupa, 1992)
Strange men they were. Soldiers, mercenaries, free-booters. Europeans all, braving the heat and dust of the merciless land of India. Some fought for wealth, some for glory, some to appease their natural craving for danger. Their glorious and ingenious exploits are filled with thrills, romance, violence and adventure. Ruskin Bond re-creates the turbulence and colour of India in the eighteenth and nineteenth centuries. The true saga of the lives and loves of these Europeans in Delhi, Jaipur, Aligarh and Lucknow often reads stranger than fiction.
Keywords: Soldiers of fortune -- India; Adventure and adventurers; India -- History, Military